(untitled) (African Journal of Biomedical Research, 2021)
High rates of mortality of reproductive-aged women, newborn and under five year old children are of global concern. This situation is worse in economically less developed areas of the world especially in Nigeria in sub-Saharan Africa and India in southern Asia. These mortalities are mostly associated with unskilled health attendance. Despite maternal, newborn and child health service designed to promote health, the mortality rates in these groups are still high in Cross River State. Therefore, this study aimed to examine how mothers utilize the services in a tertiary and a cluster of Primary Health Care facilities. Qualitative case study design was used and participants were selected through purposive sampling. Data were generated through twenty-three in-depth personal interviews of mothers and three focus group discussions with healthcare providers. Following thematic data analysis, the following five themes emerged: (1) mothers’ awareness of available maternal and child health services, (2) maternal satisfaction with services, (3) factors influencing mothers’ continuity with utilization, (4) motivators for service utilization, (5) barriers to service utilization. Family, trust in health providers and self-determination motivated service utilization. Barriers to utilization included consumers’ issue such as ignorance, fear of caesarean section and superstitious beliefs; systemic issues for example, high cost and infrastructural problems; providers’ issues like poor relational attitudes, undue delay in service delivery and staff shortage; cultural/religious issues including influence of traditional birth attendants and Church. Conclusion is that utilization of maternal and child health services is inconsistent; thus, mothers and their children are predisposed to morbidity and mortality.